Analysis of methylation features associated with neoadjuvant efficacy in HER2-positive breast cancer - Guo, Zibai; Wei, Jinhong; Gui, Anping; Liang, Xuanhua; Yu, Pengli; Bai, Jing; Cui, Liang; Xia, Xuefeng; Ma, Shihui (Frontiers in Oncology, 2025)
BackgroundResponse to trastuzumab-based neoadjuvant therapy in human epidermal growth factor receptor type 2 (HER2)-positive breast cancer is affected by multiple features of the tumor. Few studies have investigated epigenetic features in these patients. This study investigates whether changes in deoxyribonucleic acid (DNA) methylation patterns are linked to response to neoadjuvant therapy in HER2-positive breast cancer and aims to identify epigenetic markers of treatment resistance.Methods28 tumor samples were obtained from 20 HER2-positive breast cancer patients treated with neoadjuvant therapy: 12 from patients who achieved pathological complete response (pCR) before treatment, and 8 from patients who did not (non-pCR). For the non-pCR group, matched post-treatment samples were also collected, enabling paired pre- and post-treatment comparisons. After whole-genome methylation sequencing of all samples, the methylation differences between the pre-treatment pCR and non-pCR groups, as well as the methylation differences in non-pCR groups between pre-treatment and post-treatment samples were compared.ResultsBefore treatment, tumors in the non-pCR group showed slightly more hypomethylation events compared to the pCR group. After treatment, the same non-pCR tumors showed increased hypermethylation. Notably, immune-related pathways in these tumors were found to be hypermethylated, suggesting possible immune dysregulation. Methylation changes in the oncogenes MOS and RET were associated with potential resistance mechanisms. Additionally, four genes—KIT, LAD1, FAM110C, and DAPP1—were identified as candidate resistance markers based on their altered methylation patterns.ConclusionsThese findings highlight how DNA methylation changes may influence treatment outcomes in HER2-positive breast cancer and suggest novel epigenetic markers that could help predict or overcome therapy resistance.